2020
DOI: 10.1007/s10803-020-04554-9
|View full text |Cite
|
Sign up to set email alerts
|

Parent Perceptions of Caregiver-Mediated Telemedicine Tools for Assessing Autism Risk in Toddlers

Abstract: Telemedicine tools have potential for increasing access to diagnostic services for children with autism spectrum disorder (ASD). Past work has utilized tele-assessment procedures in which remote psychologists observe administration of interactive screening instruments by trained, on-site providers. Although promising, this approach relies on two clinicians, limiting its efficiency and scalability. The present study examined the use, acceptability, and parents' perceptions of two caregivermediated tools for ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 37 publications
5
99
1
Order By: Relevance
“…Providers also reported that it was beneficial to observe children and families in their home environments, interacting with familiar people and materials. Past research conducted in a laboratory setting has suggested that caregivers report tele-assessment to be comfortable and convenient, and that caregivers enjoy taking a more active role in the evaluation process (Corona et al 2020b ). Though caregiver feedback was not available for all families represented in the present study, evaluation of family satisfaction with clinical tele-assessment is ongoing and will be an essential question for future research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Providers also reported that it was beneficial to observe children and families in their home environments, interacting with familiar people and materials. Past research conducted in a laboratory setting has suggested that caregivers report tele-assessment to be comfortable and convenient, and that caregivers enjoy taking a more active role in the evaluation process (Corona et al 2020b ). Though caregiver feedback was not available for all families represented in the present study, evaluation of family satisfaction with clinical tele-assessment is ongoing and will be an essential question for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has demonstrated that many young children with ASD can be accurately identified using clinic-based tele-assessment procedures (Juárez et al 2018 ), but it is unclear how diagnostic accuracy varies within direct-to-home care. With regards to the TELE-ASD-PEDS, there is currently a large study underway examining the psychometric properties of the tool relative to traditional, gold-standard evaluations (1R21MH118539-01), and initial data support the diagnostic accuracy of the TELE-ASD-PEDS when implemented in a laboratory setting (Corona et al 2020b ). However, we have not yet validated the TELE-ASD-PEDS when administered in home settings, introducing the risk that we are missing children who should have received a diagnosis, or providing an inaccurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in-person assessments have remained drastically reduced and changed as providers work to conduct assessments in as safe and socially-distanced manner as possible. Although there is some literature showing promising results on telehealth assessments in ASD (e.g., Corona Hine et al, 2020;Smith et al, 2017), telehealth assessments need to be further examined to determine how they compare to traditional in-person assessments. It is reasonable to assume that psychometric properties such as sensitivity, specificity, and the validity of scores of diagnostic measures may change considerably in the context of telehealth.…”
Section: Introductionmentioning
confidence: 99%